Sistem Perekrutan Atlet Dayung Pusat Latihan Daerah Jawa Timur - Septian Roselina Dwi Ariani; Nia Saurina; Shofiya Syidada (Melek IT : Information Technology Journal, 2015)
Puslatda East Java Rowing is rowing regional training center located in East Java . Criteria Puslatda Rowing athletes in East Java has been determined by KONI , so not all athletes can enter in Puslatda . The recruitment of athletes rowing in this Puslatda still manually , thus making the board Puslatda difficult to determine the origin of the development and training center branch ( puslatcab ) where the candidate athletes in eastern Java . From this research came the idea to solve the problem by making Rowing Athlete Recruitment System Regional Training Centre ( Puslatda ) East Java . Results of this system , to facilitate and accelerate the paddle board Puslatda eastern Java to know the development , origin and criteria for athletes.